A Descriptive Study on the Use of Subtitling as a Didactic Tool in Translation Courses at Spanish Universities - Sonia González Cruz (University Babes-Bolyai, 2022)
In the context of translator training, subtitling has already been included into some translation curricula as an independent discipline of study aiming at training future subtitlers. Several scholars have discussed about the benefits from using subtitling as an active tool to develop students' translation competence in generic translation courses. However, there are few studies which focused on the use of active subtitling as a didactic tool in the field of translator training from a generic perspective. This article presents a descriptive study on the application of subtitling skills in generic translation courses which is carried out in the context of translator training at BA level in Spain. The main objective of this descriptive study is to present an overview on the use of subtitling in the translation classroom and analyze its level of implementation in non-audiovisual translation courses as a didactic resource that allows to develop the students' translation competence. Thus, the degree of the inclusion of subtitling into translation curricula at different Spanish universities is presented by providing data collected from questionnaires to both translation students and trainers at BA level. In this way, questionnaires not only provide relevant data about the degree of inclusion of this didactic tool in generic translation courses but also intend to collect students and trainers' experiences, opinions and expectations concerning the use of subtitling in a non-audiovisual translation context. Although the inclusion of subtitling into non-audiovisual translation courses is still quite low, the results of this study prove that subtitling leads to the activation of various general and specific competences in the translation classroom.